ANALISIS PROFITABILITAS USAHA TERNAK DOMBA KISAR DI PULAU KISAR KABUPATEN MALUKU BARAT DAYA - Inggrid Nitha Welerubun; Titik Ekowati; Agus Setiadi (MEDIAGRO, 2016)
The study aimed to analyze the profitability of Kisar sheep farmers in Kisar. The role of the livestock in the structure of income is potentially important especially in the welfare of local farmers. The study was conducted in Kisar, Kabupaten Maluku Barat Daya. The location of the study was determined intentionally (purposive) because only Kisar has the population of Kisar sheep livestock. The respondents were determined by proportionate random sampling. The chosen location was three villages named Pura-Pura, Oirata and Wonreli. The Respondents were drawn as many as 100 people were chosen randomly. The collected data were analyzed descriptively. The result of the study showed that Kisar sheep farmers’ income was IDR. 202,169.9/year for a small scale, IDR. 2307,475.2/year for a medium scale and IDR 5,391,408.9 /year for a large scale. Based on the analysis, the percentage of the profitability achieved was small scale was 20.5%, middle scale was 24.95%, and big scale was 58.25%. It is said to be profitable because the value of profitability is bigger than the bank credit interest rate of 5%.   Keywords: Profitability, income breeding sheep Kisar